2019
DOI: 10.1074/jbc.ra119.010356
|View full text |Cite
|
Sign up to set email alerts
|

Glucose stimulates microRNA-199 expression in murine pancreatic β-cells

Abstract: MicroRNA 199 (miR-199) negatively impacts pancreatic β-cell function and its expression is highly increased in islets from diabetic mice as well as in plasma of diabetic patients. Here we investigated how miR-199 expression is regulated in β-cells by assessing expression of miR-199 precursors (primiR-199a1, primiR-199a2, and primiR-199b) and mature miR-199 (miR-199-3p and miR-199-5p) and promoter transcriptional activity assays in mouse islets and mouse insulinoma cells (MIN6) under different stimuli. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 49 publications
2
3
0
Order By: Relevance
“…In previous work, the miR-216a knockout mouse was reported to have defects in insulin secretion in the context of chronic high-fat diet (77), and miR-25 has been described as a negative regulator of insulin synthesis in INS-1 cells, a rat beta cell line (64). As another example, we show that miR-199b-5p is associated with T2D status, consistent with a previous study in murine beta cells where miR-199b-5p was shown to be highly responsive to glucose stimulation (78). We also find that miR-21-5p is strongly associated with T2D status.…”
Section: Discussionsupporting
confidence: 92%
“…In previous work, the miR-216a knockout mouse was reported to have defects in insulin secretion in the context of chronic high-fat diet (77), and miR-25 has been described as a negative regulator of insulin synthesis in INS-1 cells, a rat beta cell line (64). As another example, we show that miR-199b-5p is associated with T2D status, consistent with a previous study in murine beta cells where miR-199b-5p was shown to be highly responsive to glucose stimulation (78). We also find that miR-21-5p is strongly associated with T2D status.…”
Section: Discussionsupporting
confidence: 92%
“…In previous work, the miR-216a knockout mouse was reported to have defects in insulin secretion in the context of chronic high-fat diet ( 90 ), and miR-25 has been described as a negative regulator of insulin synthesis in INS-1 cells, a rat insulinoma cell line ( 75 ). As another example, we show that miR-199b-5p is associated with T2D status, consistent with a previous study in murine beta cells where miR-199b-5p was shown to be highly responsive to glucose stimulation ( 91 ). We also find that miR-21-5p is strongly associated with T2D status.…”
Section: Discussionsupporting
confidence: 92%
“…As miR-199 was reported to be dysregulated in cancer from all these organs [35][36][37] , the corresponding mechanisms responsible for the dysregulation of miR-199 may be also different. Moreover, in mouse islets, miR-199a-3p is from both miR-199a-1 and miR-199a-2, but not miR-199b, and the pri-miR-199a-1 is about 30% more than pri-miR-199a-2, whose expression are regulated by glucose metabolism and calcium influx 38 . Thus, why miR-199-3p is expressed from different gene locus in different organs and the underlying biological significance are interesting topics, which still need further exploration.…”
Section: Discussionmentioning
confidence: 92%